The Relationship between Knowledge and Attitudes with the Behavior of Health Workers in Medical Waste Management in Indonesia: A Systematic Review and Islamic Perspectives - Lutvia dini Faghfirlia; Kholis Ernawati; Andri Gunawan; Rita Komalasari (Junior Medical Journal, 2022)
During the Covid-19 pandemic, there was an increase in medical waste, especially in healthcare facilities. Medical waste, if not managed properly, will potentially pollute the environment. The behavior of health workers in managing medical waste is influenced by knowledge and attitudes. The study aimed to analyze the relationship between knowledge and attitudes with the behavior of health workers in managing medical waste in Indonesia using a systematic review approach and according to an Islamic perspective. This study uses the method of literature review and systematic review. The selection of articles used the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method on the Google Scholar journal website. Search for articles with the keyword